Difference of Socio-Economic Characteristics based on Food Security Levels in Urban and Rural Poor Household in South Sulawesi - Ashari, Chica Riska; Khomsan, Ali; Baliwati, Yayuk Farida (Jurnal Dunia Gizi, 2019)
Backgorund; Nutritional problems arise due to the problem of food security at the household level, namely the ability of households to obtain food for all household members. This reflects the lack of accessibility of households to obtain food, one of which is caused by poverty. Many factors can affect household food security. Aim; This study aims to analyze differences in socio-economic characteristics based on the level of food security of poor urban and rural households in South Sulawesi as measured by the HFIAS Method and the modified Maxwell Method. Method; This study used a cross sectional design. Sampling using purposive sampling with a sample size of 170 households. Data analysis performed was bivariate analysis with t-independent test and chi square test. Results; The results showed that the variables that had differences between food-security and food-insecurity household groups as measured by the HFIAS method were household size (p = 0,000), while variables that had differences between household groups were food-security and food-insecurity (0.029) and household size (p = 0.000). Conclusions; Household size variables have differences between food-security and food-insecurity household groups as measured by the HFIAS method and the modified Maxwell method. Household size is an important variable that affects the level of household food security.